The effect of the strategy of withdrawing numbers on the scientific vigilance of the fourth primary school girls in science (Journal of the College of Basic Education, 2022)
The aim of the research is to identify (the effect of the number-pulling strategy on the scientific vigilance of fourth-grade students in science), by verifying the formulation of the following null hypothesis: (There are no statistically significant differences at the level of significance (0,05) between the average An experimental design with two experimental and control groups with a post-test of the scientific vigilance scale was chosen, and it represented the current research community with all fourth-grade primary schoolgirls in the primary schools of the Baghdad Education Directorate / Al-Rusafa Third for the academic year (2021-2022) AD, and (Al-Kahla Elementary for Girls) was chosen to represent The research sample, whose number of students is (64) students divided into two study divisions (A, B), two divisions were chosen by simple random assignment (B, A) as a sample for the research and there were no failed students, and it was (32) students for the experimental group (B) that were studied According to the strategy of drawing numbers, and (32) female students of the control group (A), which were studied according to the usual method. scores of the experimental group students who were studied according to the number-pull strategy and the average scores of the control group students who were studied according to the usual method in the scientific vigilance scale).The two groups were rewarded in the variables (intelligence, previous achievement, prior information, scientific vigilance), and the experiment was conducted in the first semester of the academic year (2021-2022).After the end of the experiment and application and obtaining the measured results, the data were treated statistically using the t-test for two independent samples, and the following results were reached:(The students of the experimental group who were studied according to the strategy of drawing numbers outperformed the students of the control group who were studied according to the usual method in the scientific vigilance scale). Therefore, the researcher recommends some recommendations and suggestions.